Impaired cardiac mitochondrial function and contractile reserve following an acute exposure to environmental particulate matter - Marchini, Timoteo Oscar (2013)
BACKGROUND: It has been suggested that mitochondrial function plays a central role in cardiovascular diseases associated with particulate matter inhalation. The aim of this study was to evaluate this hypothesis, with focus on cardiac O2 and energetic metabolism, and its impact over cardiac contractility. METHODS: Swiss mice were intranasally instilled with either residual oil fly ash (ROFA) (1.0 mg/kg body weight) or saline solution. After 1, 3 or 5 h of exposure, O2 consumption was evaluated in heart tissue samples. Mitochondrial respiration, respiratory chain complexes activity, membrane potential and ATP content and production rate were assessed in isolated mitochondria. Cardiac contractile reserve was evaluated according to the Langendorff technique. RESULTS: Three hours after ROFA exposure, tissue O2 consumption was significantly decreased by 35% (from 1180 +/- 70 to 760 +/- 60 ng-at O/min g tissue), as well as mitochondrial rest (state 4) and active (state 3) respiration, by 30 and 24%, respectively (control state 4: 88 +/- 5 ng-at O/min mg protein; state 3: 240 +/- 20 ng-at O/min mg protein). These findings were associated with decreased complex II activity, mitochondrial depolarization and deficient ATP production. Even though basal contractility was not modified (control: 75 +/- 5 mm Hg), isolated perfused hearts failed to properly respond to isoproterenol in ROFA-exposed mice. Tissue O2 consumption rates positively correlated with cardiac contractile state in controls (r2 = 0.8271), but not in treated mice (r2 = 0.1396). GENERAL SIGNIFICANCE: The present results show an impaired mitochondrial function associated with deficient cardiac contractility, which could represent an early cardiovascular alteration after the exposure to environmental particulate matter.